Aggression Towards Caregivers in Parkinson's Disease and Related Disorders: A Mixed Methods Study. Issue 7 (7th September 2022) - Macchi, Zachary A.; Seshadri, Sandhya; Ayele, Roman; Bock, Meredith; Long, Judith; Coats, Heather; Miyasaki, Janis; Pantilat, Steven Z.; Katz, Maya; Santos, Elizabeth J.; Sillau, Stefan H.; Lum, Hillary D.; et al.
ABSTRACT: Background: Aggression is one manifestation of behavioral disturbances in neurodegenerative disease with emerging literature suggesting a high prevalence in Parkinson's disease and related disorders (PDRD). Objectives: Our aim was to describe characteristics, associated factors, and consequences of aggression towards caregivers in PDRD. Methods: This is a convergent mixed methods study, leveraging data from 296 PDRD patient–caregiver dyads in a clinical trial of palliative care and semi‐structured interviews with a subgroup of 14 caregivers who reported aggression. The primary outcome was baseline caregiver‐reported aggression. Using multivariate linear regression, baseline dyad characteristics (eg, measures of disease, psychosocial issues, caregiver strain) were examined to identify factors associated with aggression. Thematic analysis of interviews was used to augment these findings. Results: Associated variables included disease duration ( r = 0.15, P < 0.05), patient grief ( r = 0.22, P < 0.001), symptom burden ( r = 0.18, r < 0.01), resistance to care ( r = 0.40, P < 0.01), caregivers' depression ( r = 0.16, P < 0.05), and caregiving burden ( r = 0.34, P < 0.001). We identified five themes: (1) Aggressive behaviors range from verbal abuse to threats of physical violence; (2) Caregivers believe that aggressive behaviors result from the difficulty patients experience in coping with disease progression and related losses; (3) Caregivers' stress and mental health are worsened by aggressive behaviors; (4) Aggressive behaviors negatively affect patient–caregiver relationships; (5) Caregivers are ill‐prepared to manage aggressive behaviors and cope with the consequences on their own. Conclusions: Aggression in PDRD is driven by diverse factors (eg, grief, fluctuations in cognition) with serious consequences for caregivers. Neurologists and movement specialists should consider screening for aggression while prioritizing caregiver education and wellbeing.